2021
DOI: 10.1042/bsr20202296
|View full text |Cite
|
Sign up to set email alerts
|

Reference values and the effect of clinical parameters on thyroid hormone levels during early pregnancy

Abstract: Objective: Thyroid dysfunction is a common endocrine problem during pregnancy; correct diagnosis and appropriate treatments are essential to avoid adverse pregnancy outcomes. Besides, it is vital to identify and quantify the major risk factors for gestational thyroid dysfunction, including thyroid autoimmunity, human chorionic gonadotropin (HCG) concentration, body mass index (BMI) and parity. The study objective was to establish reference ranges during early pregnancy and to explore the relationship between r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…At the same time, after applying a Pearson analysis, we found that the levels of TC, TG and LDL-C were positively correlated with those of TSH and with the pregnancy outcomes; and, that the TSH levels were positively correlated with the pregnancy outcomes. Lin H et al 27 showed that TSH was significantly and positively associated with TG (P=0.03), which is consistent with this result, but they also found that serial TSH, free thyroxine (FT4) and free triiodothyroxine (FT3) in a Chinese population, and demonstrated that BMI ≥ 23kg/ m2, material degree ≥ three and material age ≥ 30 years may increase the risk of thyroid dysfunction. Our study showed that there is no significant difference in age and gestational week between the two groups, which may be related to the selection of sample size.…”
Section: Discussionsupporting
confidence: 62%
“…At the same time, after applying a Pearson analysis, we found that the levels of TC, TG and LDL-C were positively correlated with those of TSH and with the pregnancy outcomes; and, that the TSH levels were positively correlated with the pregnancy outcomes. Lin H et al 27 showed that TSH was significantly and positively associated with TG (P=0.03), which is consistent with this result, but they also found that serial TSH, free thyroxine (FT4) and free triiodothyroxine (FT3) in a Chinese population, and demonstrated that BMI ≥ 23kg/ m2, material degree ≥ three and material age ≥ 30 years may increase the risk of thyroid dysfunction. Our study showed that there is no significant difference in age and gestational week between the two groups, which may be related to the selection of sample size.…”
Section: Discussionsupporting
confidence: 62%
“…Thyroid hormones play a crucial role in fetal development, and thyroid hormone levels in pregnant women in Zunyi were low compared to other studies. For example, one study found thyrotropin levels in pregnant women in the first trimester of pregnancy to be 0.11–3.67 mIU/L, FT3 levels to be 3.19–5.91 pmol/L, and FT4 levels to be 10.95–16.79 pmol/L; furthermore, a birth cohort in Beijing found that early pregnancy TSH concentrations were 0.74–5.46u IU/mL, FT3 early pregnancy concentrations of 3.82–5.34 pmol/L, and FT4 early pregnancy concentrations of 12.94–20.58 pmol/L . This phenomenon may be related to environmental and dietary factors in Zunyi, such as endemic iodine deficiency and frequent consumption of pickles and cured meat.…”
Section: Discussionmentioning
confidence: 99%